Inflammation but Not Endothelial Dysfunction Is Associated with the Severity of Coronary Artery Disease in Dyslipidemic Subjects - Christian F. Rueda-Clausen; Patricio López-Jaramillo; Carlos Luengas; Maria del Pilar Oubiña; Victoria Cachofeiro; Vicente Lahera (Hindawi Limited, 2009)
Introduction. Endothelial dysfunction and inflammation play a key role in the development of atherosclerosis. The present study evaluated endothelial function, inflammatory parameters, and carotid intima-media thickness (IMT) in dyslipidemic patients with or without coronary artery disease (CAD). Methods. Metabolic profile and inflammatory parameters were determined in dyslipidemic patients with (+CAD, n=33) and without (−CAD, n=69) symptomatic CAD. Endothelial function was evaluated by flow mediated dilatation (FMD) and plasma concentration of nitrites and nitrates. Carotid IMT was measured by ultrasound. Results. No significant differences were observed in anthropometric hemodynamic or metabolic parameters between the groups. After adjusting by age and medication usage, some inflammatory markers were significantly higher in +CAD; however no significant differences in FMD or plasma levels of nitrites were observed. Conclusions. In subjects with dyslipidemia, the presence of CAD is associated with an elevation of certain inflammatory markers and carotid IMT but not with further endothelial dysfunction.